PERANCANGAN MANAJEMEN KINERJA PENYELENGGARAAN PENDIDIKAN DAN PELATIHAN DENGAN ANCANGAN MANAGEMENT BY OBJECTIVES (MBO) DAN PERSPEKTIF BALANCED SCORECARD - Ika Susanti; Aida Vitaya Hubeis; Sadikin Kuswanto (Jurnal Manajemen & Agribisnis, 2012)
This research is aimed to make a performance management design based on MBO and Balanced Scorecard perspective approach in order to improve education and training administration. Performance accountability stimulates public sector organizations to improve their performance continuously and to build a performance management system that is oriented not only toward the budget and its realization, but also toward results. This paper discusses MBO and Balanced Scorecard perspective approach in planning and controlling its programs. In addition, this model can be used as a strategic controller for the management to measure the organization’s success and failure. This is a qualitative research approached by a case study using the method of participant observation through questionnaires, in depth-interviews, and focused group discussions. The success of education and training administration is determined by performance achievements of the individual, division, and organization that include financial aspect, participants of the education and training program, Standard Operating Procedure (SOP), administrators of the program, technology, and innovation. The resulted design is a four-stage flowchart describing planning, implementation, measurement, and performance evaluation.Keywords : Performance Management, Design, Education and Training, Management by Objectives (MBO), Balanced Scorecard Perspective